Dimenzije trajnosti - Vovk Korže, Ana (Revija za geografijo, 2011)
Sustainable development is generally understood as an approach that has a great role in connection of environmental, economical and social politics in order to control the natural resource use, create redirection of current politics of farm subventions, traffic and energy resources into more sustainable direction. In recent decades has current approach only created more problems and threatened to all life on Earth. This is why sustainability has to be clearly redefined. Sustainability has more dimensions: ecosystematical (this dimension is coherent with the ecosystematical approach and can be reffered as the most important dimension of sustainability); integrity (failure of sustainable development is so called schism between economical, social, ecological, human and local development and supporting of each individual, but only partial item); welfare (economical growth, directed to the production of material goods should not so fataly affect the society and nature processes as it does now); self-suply with the inclusion of publicity (activation of all available potentials, their connections and motivations as well the law regulations).
Keywords: ecology; ekologija; naravni viri; okoljevarstvena politika; sustainable development; trajnostni razvoj